EFFECTIVE TEACHING OF PHYSICAL EDUCATION TO LEARNERS WITH VISUAL DISABILITY: A LITERATURE REVIEW - Jakinda, Rose; Munayi, Simon; Chumba, Janet; Gathoni, Benson (Journal of Education and Practice, 2022)
Purpose: The value of effective teaching of physical education to any learners cannot be over emphasized. Physical education is recognized by both the United Nations and World Health Organization as a fundamental in the fight against life style diseases. Learners with disability in Africa have received a raw deal when it comes to the teaching of physical education. Methodology: A desktop literature review was used for this purpose. , a systematic search was carried out using Google Scholar, Semantic Scholar, and Research Gate. This paper reviews literature from around the world in an attempt to assess what scholars consider effective teaching for learners with visual disability. Findings: The paper defines what effective teaching of physical education entail, before delving into what effective teaching of physical education for learners with visual disability is. The study assesses the props that make effecting teaching of physical education which include: the personnel involved in teaching PE, Instructional methods, the place of equipment/ facilities in teaching physical education, administrative support for the teaching of physical education and the attitudes of the learners and the staff in the teaching of physical education. This paper concludes that effective teaching entails effort and creativity for the learners with visual disability to benefit. Unique Contribution to Theory, Practice and Policy recommendation: The paper recommends an assessment of the current situation in the teaching of physical education for learner's with visual disability. All learners should learn the same units, with modifications when necessary, typically receiving an equal amount of instruction per week as their sighted peers, or more. Training should be offered as skilled peer tutors and paraeducators can be a resource to assist with games, fitness, or other activities when needed.